Resilient protein co-expression network in male orbitofrontal cortex layer 2/3 during human aging - Pabba, Mohan (Neurobiol Aging, 2017)
The orbitofrontal cortex (OFC) is vulnerable to normal and pathological aging. Currently, layer resolution large-scale proteomic studies describing “normal” age-related alterations at OFC are not available. Here, we performed a large-scale exploratory high-throughput mass spectrometry-based protein analysis on OFC layer 2/3 from 15 “young” (15–43 years) and 18 “old” (62–88 years) human male subjects. We detected 4,193 proteins and identified 127 differently expressed proteins (DE) (p-value ≤0.05; effect size >20%), including 65 up- and 62 down-regulated proteins (e.g., GFAP, CALB1). Using a previously-described categorization of biological aging based on somatic tissues, i.e., peripheral “hallmarks of aging”, and considering overlap in protein function, we show highest representation of altered cell-cell communication (54%), deregulated nutrient sensing (39%) and loss of proteostasis (35%) in the set of OFC layer 2/3 DE proteins. DE proteins also showed a significant association with several neurological disorders, e.g., Alzheimer’s disease and schizophrenia. Notably, despite age-related changes in individual protein levels, protein co-expression modules were remarkably conserved across age groups, suggesting robust functional homeostasis. Collectively, these results provide biological insight into aging and associated homeostatic mechanisms that maintain normal brain function with advancing age.